JOB INVOLVEMENT AND SERVANT LEADERSHIP INFLUENCE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) IN EMPLOYEES - Tentama, Fatwa; Salsabila, Andi Lutfiyah Nada (Jurnal Psikohumanika, 2023)
This study aims to test job involvement and servant leadership influence on Organizational Citizenship Behavior (OCB) in employees. Participant in this research was 70 permanent employees in an "X" Automotive company in Yogyakarta who had worked a minimum of one year. The data collection used OCB, job involvement, and servant leadership scales. The research data were analyzed using multiple linear regression assisted by SPSS program V.21. The result of simultaneous data analysis indicates that job involvement and servant leadership could influence Organizational Citizenship Behavior (OCB) (F = 406.135, p = 0.000). The partial data analysis shows job involvement (Standardized Coefficients = 0.536, p = 0.000) and servant leadership (Standardized Coefficients = 0.440, p = 0.000), respectively, influence on Organizational Citizenship Behavior (OCB). Job involvement and servant leadership simultaneously contribute as much as 92 % to Organizational Citizenship Behavior (OCB). Job involvement contributes 51%, and servant leadership contributes 41%. Therefore, it can be concluded that an internal factor, job involvement, and an external factor, servant leadership, influence the formation of Organizational Citizenship Behavior (OCB). The internal factor of job involvement is more dominant than the external factor of servant leadership in affecting Organizational Citizenship Behavior (OCB).